Determinants of Small Medium Enterprises (SMEs) competitiveness in the global market” - Darsono, Susilo Nur Aji Coko; Akhbar, Taufik; Ibrahim, Khairunisah; Kurniawan, Dhika Amalia; ., Hendar (UMY Press, 2020)
The challenges faced by Small medium enterprises (SMEs) are growing rapidly and pushing the firms to improve their competitiveness to enhance the levels of productivity and the existence in international markets. Global challenges, open market competition and information technology develop-ment are the barriers and opportunities they may take advantage of, to be winners in the dynamic global markets. To that end, a survey was carried out in Yogyakarta Province, Indonesia. This chapter aims to identify the key suc-cess factors that influence the competitiveness of SMEs in the globalization era through the challenges that will be faced in the near future. Principle Component Analysis was applied to determine the structure of relationships between many variables in the form of components. Components formed are random quantities that previously cannot be observed, measured and determined directly. This chapter contributes to the theoretical and manage-rial implications on SMEs competitiveness. The main results found that the three components which determined the SMEs competitiveness are Knowl-edge Based Resources, Business Performance, and Operational Effectiveness and Innovations.